2014
DOI: 10.1021/jo501013p
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Physical Interpretation of Substituent Effects: The Case of Fluorine and Trifluoromethyl Groups

Abstract: The application of ab initio and DFT computational methods at six different levels of theory (MP2/cc-pVDZ, MP2/aug-cc-pVTZ, B3LYP/cc-pVDZ, B3LYP/aug-cc-pVTZ, M06/cc-pVDZ, and M06/aug-cc-pVTZ) to meta- and para-substituted fluoro- and trifluoromethylbenzene derivatives and to 1-fluoro- and 1-trifluoromethyl-2-substituted trans-ethenes allowed the study of changes in the electronic and geometric properties of F- and CF3-substituted systems under the impact of other substituents (BeH, BF2, BH2, Br, CFO, CHO, Cl, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 90 publications
(127 reference statements)
1
61
0
Order By: Relevance
“…Moreover, the cSAR approach can be applied to both, the varying substituents, [as cSAR(X)], as well as to the reaction site (or a fixed functional group in the series X-R-Y), [cSAR(Y)], and allows to estimate the regression line cSAR(Y) vs. cSAR(X). The slope of this regression describes the strength of interactions between X and Y [9,10]. It was also shown that changes in geometry of the components of the functional group Y correlate well with cSAR(Y) [12] and hence correlate also with cSAR(X) that was documented for aniline [10], nitrobenzene [13], and benzoic acid [14] substituted derivatives.…”
Section: ) Is Alwaysmentioning
confidence: 79%
See 2 more Smart Citations
“…Moreover, the cSAR approach can be applied to both, the varying substituents, [as cSAR(X)], as well as to the reaction site (or a fixed functional group in the series X-R-Y), [cSAR(Y)], and allows to estimate the regression line cSAR(Y) vs. cSAR(X). The slope of this regression describes the strength of interactions between X and Y [9,10]. It was also shown that changes in geometry of the components of the functional group Y correlate well with cSAR(Y) [12] and hence correlate also with cSAR(X) that was documented for aniline [10], nitrobenzene [13], and benzoic acid [14] substituted derivatives.…”
Section: ) Is Alwaysmentioning
confidence: 79%
“…By definition, cSAR(X) is a sum of atomic charges at all atoms of the substituent and the ipso carbon atom [7]. This descriptor correlates well with substituent constants [7][8][9][10]. It is important to stress that the cSAR(X) approach realized by the use of different atomic charge schemes leads to the results which are, as a rule, mutually well correlated [11].…”
Section: ) Is Alwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…cSAR(X) is a sum of atomic charges of X and of the ipso atom (carbon or nitrogen in our case) to which the substituent is attached. It was shown that cSAR(X) values correlate well [15,[19][20][21][22] with the Hammett substituent constants [13]. Moreover, it was documented that cSAR of a functional group (NO and NMe 2 ) in para-substitute d d e r i v a t i v e s o f n i t r o s o b e n z e n e a n d N , Ndimethylaminebenzene nicely describes changes in the geometry in these groups [23].…”
Section: Introductionmentioning
confidence: 91%
“…The other face of intramolecular interactions described as substituent effects is named reverse substituent effect. This means that electron-donating/electronattracting properties of X depend on the kind of R-Y part of the molecule [15][16][17]. A great number of various substituent constants (see a complete collection of them in [13]) are just a result of this kind of interactions.…”
Section: Introductionmentioning
confidence: 99%